The Penalty for Blasphemy against the Infallibles and its Reconciliation with their Practical Conduct - ?????? ?????, ??? ????; ??????, ??????? (???????? ??????? ?????? ????)
The penalty for blasphemy against the holy Prophet and the Infallibles prescribed by the Shiite Jurists based on the hadiths is the obligation of killing the blasphemer and that his blood may be shed with impunity. Nonetheless, there are a variety of cases in the infallibles' practical conduct where they have treated the blasphemer nobly and with tolerance and prevented their companions from executing the death penalty. The authors, with a view to resolve the above said contradiction, have reviewed and analyzed the hadiths underlying the death penalty for the blasphemer and concluded that up to the certainty of the referred proofs is the obligation of killing the blasphemer who has targeted the holy Prophet?s prophethood position. In case the subject matter of hadiths is extended to those who blaspheme the Imams, the death penalty concerns the rancorous persons and blasphemers who knowingly and intentionally insult the Imam's legal personality and Imama position. Therefore, there is no conflict between the religious ruling of punishing the blasphemer and the Infallibles' practical conduct in the form of treating morally and generously those who unknowingly insult them and, out of ignorance, were hostiles to their individual personality.